Correlation of boswellic acids with antiproliferative, antioxidant and antimicrobial activities of topographically collected Boswellia serrata oleo-gum-resin - Madhuri Gupta; Shilpi Singh; Alka kurmi; Suaib Luqman; Dharmendra Saikia; Moni Thomas; Prasant Kumar Rout (Phytomedicine Plus, 2022)
Background: : Boswellia serrata, an economically vital ethnic tree of dry deciduous forests to provides oleo-gum-resin of pharmaceutical significance. The marker molecules of this resin are penta-cyclic tri-terpenoids commonly known as boswellic acids (BAs). Methods: : The topographical oleo-gum-resin samples were used for chemo-profiling of the BAs in methanol extracts by HPLC analysis. The anti-proliferative potential of extracts was evaluated on eight cell lines by MTT assay. The antibacterial activity was evaluated by the disk diffusion process and Minimum inhibitory concentrations (MIC) of extracts were performed by the microdilution assay. The antioxidant potentials of extract samples were accomplished by DPPH scavenging and ABTS assays. Results: : The sample collected from Haldwani (BS-H) has been given the good yield of the extract (65.1%) with the lowest percentage of BAs (9.6%). Shivpuri, Neemuch, and Mandsaur are topographical locations in the state of Madhya Pradesh (M.P.) and are distinguished as the oleo-gum-resin trading sites in India. The methanol extract of Neemuch collection (BS-N2) was contained enhanced percentage of KBA (keto-β-boswellic acid) (8.4%) with highest yield of the extract (70.1%), while Mandsaur collection (BS-M1) was contained the highest percentage of AKBA (6.9%) with enhanced amount of BAs (39.89%). The extracts of M.P. samples have been shown inhibition of lung cancer cell-line with IC50: 2.34–13.06 µg/mL, and the percent inhibition is ranged from 7.0 to 93.67%. All these extracts have been displayed significant antimicrobial activity against Mycobacterium smegmatis (MS) (MIC: 2.4–156 µg/mL). Most importantly, Mandsaur (BS-M1) and Neemuch (BS-N2) collections have shown significant activity against Methicillin-resistant Staphylococcus epidermidis (SE) strain with MIC of 2.4 µg/mL. All the extracts were shown significant antioxidant activity with IC50: 2.7–9.9 µg/mL, and BS-N2 was displayed 78.4% of free radical scavenging reduction activity. Similarly, ABTS was complemented the DPHH scavenging assay. Cluster correlation analyses of chemo-types with biological activities were performed among the different topographical samples. Conclusion: : The variations of activities among the extracts were related to their chemical compositions. The topographical samples with the improved percentage of KBA and AKBA were shown highly significant anticancer, antibacterial and antioxidant activities. Cluster correlation analyses of all samples were assisted to compare the BAs contents with bioactivities.